L’ayahuasca et son ombre. L’apprentissage de la possession dans un centre chamanique d’Amazonie péruvienne - David Dupuis (Journal de la Société des Américanistes)
Takiwasi is both an addiction treatment clinic and one of the main “shamanic centers” of the Peruvian Amazon. Every year, an international clientele participates in courses involving the ritualized use of emetic preparations and the psychotropic beverage ayahuasca, retreats in the jungle, conferences and speech groups. The proposed practices seem to lead those who are willing to perceive themselves as influenced, attacked and inhabited by malevolent forces that are usually invisible. Some of them also report the experience of “possession” sequences, occurring during ayahuasca rituals. In this article, the author proposes to question the surprising place occupied by possession in a cure presented as “shamanic”. Then, based on the ethnographic description of a participant’s ritual journey, he tries to shed light on the underpinnings of the appropriation of these motifs and its implications, both in terms of symbolic recomposition of identity and the dynamics of cultural transmission.